2020
DOI: 10.1016/j.brs.2020.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Deep brain stimulation of the nucleus accumbens for treatment-refractory anorexia nervosa: A long-term follow-up study

Abstract: Background: Given that anorexia nervosa (AN) is a life-threatening mental disorder and has poor clinical outcomes, novel effective treatments are warranted, especially for severe and persistent cases. Objective: To investigate the safety, feasibility, and clinical outcomes of using deep brain stimulation (DBS) of the nucleus accumbens (NAcc) in treatment-refractory AN patients. Methods: A total of 28 women with refractory AN underwent NAcc-DBS and completed this 2-year follow-up study. The clinical outcomes, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(71 citation statements)
references
References 30 publications
1
63
0
1
Order By: Relevance
“…These two trials also demonstrated glucose metabolism changes after DBS in the NAcc and SCC by positron emission tomography [96,97]. Recently, the Shanghai group published the largest series on DBS in AN involving 28 patients with refractory AN who were followed for at least 2 years after electrode implantation in the NAcc [98]. All patients had a major psychiatric comorbidity at inclusion (n = 9 OCD, n = 7 severe anxiety, and n = 12 MDD).…”
Section: Deep Brain Stimulation In Anorexia Nervosamentioning
confidence: 92%
See 1 more Smart Citation
“…These two trials also demonstrated glucose metabolism changes after DBS in the NAcc and SCC by positron emission tomography [96,97]. Recently, the Shanghai group published the largest series on DBS in AN involving 28 patients with refractory AN who were followed for at least 2 years after electrode implantation in the NAcc [98]. All patients had a major psychiatric comorbidity at inclusion (n = 9 OCD, n = 7 severe anxiety, and n = 12 MDD).…”
Section: Deep Brain Stimulation In Anorexia Nervosamentioning
confidence: 92%
“…All patients had a major psychiatric comorbidity at inclusion (n = 9 OCD, n = 7 severe anxiety, and n = 12 MDD). Post-hoc analysis suggests that NAcc DBS is less effective for weight restoration in the binge/purge AN subtype than in the restrictive subtype [98]. Another recent preliminary study proposes for the first time two targets in the same trial chosen according to the main psychiatric comorbidities associated with AN: SCC for affective disorder (n = 4) and NAcc for anxiety disorder (n = 4) (Martinez et al, 2020).…”
Section: Deep Brain Stimulation In Anorexia Nervosamentioning
confidence: 99%
“…Overall, the parallels drawn in the current paper serve as a point of contemplation and discussion, and provide a logical stepping stone in order to further study and better understand the neurobiological underpinnings of CHSP. In AN, the implication of neurobiological research in the field of eating disorders has led to treatments focusing on the potential of neuromodulation, such as Transcranial Magnetic Stimulation (TMS) [19,20], trans-Cranial Direct Current Stimulation (tDCS) [19], and deep brain stimulation (DBS) [21]. In addition, psychotherapeutic treatments which target the biological basis for the maintenance of maladaptive, including eating pathology and AN-centric behaviours [22] have also been developed as a result of the increased knowledge of neurobiological functioning in eating disorders.…”
Section: Future Directionsmentioning
confidence: 99%
“…The somatic condition and the potential development of a refeeding syndrome should be closely monitored by a physician. Wei Liu et al [15] revealed that the NAcc-DBS was less effective for weight restoration in patients with the bingeeating type of AN than in those with the restricting subtype (R-AN). There were noted, compared to presurgical levels, significant increases in BMI and improvement in psychiatric scale stores during the 6-month follow-up of 28 patients with AN and the results were maintained at the 2-year review.…”
Section: Anorexia Nervosamentioning
confidence: 99%
“…Wei Liu i inni [15] wykazali, że NAcc-DBS był mniej skuteczny w przywracaniu masy ciała u pacjentów z podtypem AN z napadowym objadaniem się niż u pacjentów z podtypem restrykcyjnym (R-AN). Podczas 6 miesięcznej obserwacji 28 pacjentów z AN odnotowano znaczący wzrost BMI i poprawę wyników w skali psychiatrycznej w porównaniu z poziomami przedoperacyjnymi, a wyniki utzymywały się przez 2 lata trwania badania.…”
Section: Jadłowstręt Psychicznyunclassified